A qualitative study exploring hospital-based team dynamics in discharge planning for patients experiencing delayed care transitions in Ontario, Canada - Lauren Cadel; Jane Sandercock; Michelle Marcinow; Sara J. T. Guilcher; Kerry Kuluski (BMC, 2022)
Abstract Background In attempt to improve continuity of patient care and reduce length of stay, hospitals have placed an increased focus on reducing delayed discharges through discharge planning. Several benefits and challenges to team-based approaches for discharge planning have been identified. Despite this, professional hierarchies and power dynamics are common challenges experienced by healthcare providers who are trying to work as a team when dealing with delayed discharges. The objective of this study was to explore what was working well with formal care team-based discharge processes, as well as challenges experienced, in order to outline how teams can function to better support transitions for patients experiencing a delayed discharge.  Methods We conducted a descriptive qualitative study with hospital-based healthcare providers, managers and organizational leaders who had experience with delayed discharges. Participants were recruited from two diverse health regions in Ontario, Canada. In-depth, semi-structured interviews were conducted in-person, by telephone or teleconference between December 2019 and October 2020. All interviews were recorded and transcribed. A codebook was developed by the research team and applied to all transcripts. Data were analyzed inductively, as well as deductively through directed content analysis. Results We organized our findings into three main categories - (1) collaboration with physicians makes a difference; (2) leadership should meaningfully engage with frontline providers and (3) partnerships across sectors are critical. Regular physician engagement, as equal members of the team, was recommended to improve consistent communication, relationship building between providers, accessibility, and in-person communication. Participants highlighted the need for a dedicated senior leader who ensured members of the team were treated as equals and advocated for the team. Improved partnerships across sectors included the enhanced integration of community-based providers into discharge planning by placing more focus on collaborative practice, combined discharge planning meetings, and having embedded and physically accessible care coordinators in the hospital. Conclusions Team-based approaches for delayed discharge can offer benefits. However, to optimize how teams function in supporting these processes, it is important to consistently collaborate with physicians, ensure senior leadership engage with and seek feedback from frontline providers through co-design, and actively integrate the community sector in discharge planning.